INFORMATION SYSTEM DESIGN IN SKALA RHEKA - Wishnu Kurniawan; Drs. Eko Hadiyanto, MM (Jurnal Sistem Informasi, 1997)
A system can be said to be good, if such information or can provide a certain report to the needy is a good and timely. From the analysis of the current system in the company Skala Rheka, there are several obstacles such as slow process of preparation of reports, lack of employment natty management. Therefore, in order to facilitate the borrowing of these files by creating better systems and computerized.